The Peculiarities Of The Need Sphere Of Accentuation Types Of Character - Araqelyan, Anna (Զանգակ հրատ.)
From the point of psychology, the structure of personality and character gives an opportunity to observe people discovering new points for solving problems and overcoming new problems. How can character and need structure be connected? The research on discovering and inventing the relation between character and need structure helps find new ways while examining every type of person from the point of need structure. Need structure allows us to know the needs of each psychological personality type, and it is beneficial for meeting people. The peculiarities of the need sphere of the emphasized personality type are the stepping stone for the good relationship between the character and the need structure. The article presents the results of a survey conducted with 139 students aged 18- 19. The study aimed to identify the characteristics of the main groups of needs and their components in emphasized personality types. The article analyzes the peculiarities of the relationship between emphasized personality types and basic needs.
Keywords: Psychology